2006
DOI: 10.1016/j.icesjms.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The feeding behaviour of cultured and wild Atlantic salmon, Salmo salar L., in the Louvenga River, Kola Peninsula, Russia

Abstract: An underwater survey was conducted in the Louvenga River to investigate the behaviour and distribution of juvenile Atlantic salmon, Salmo salar L., and the adaptation of cultured fish to the natural environment. The food and feeding habits of 34 wild and 44 cultured parr released from the Kandalaksha hatchery were also studied. The cultured salmon fed mostly in the bottom 15 cm of the water column in current velocities of 0.2e0.35 m s À1 . In contrast to wild fish, when cultured fish moved away from these area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…Although poor in absolute numbers of OTUs (that is, richness), diversity estimates from returning adults were not significantly different from juveniles, suggesting a fairly even frequency distribution of those OTUs present. Dietary complexity in juvenile salmonids could explain rich associated microbial assemblages (Orlov et al, 2006). Meanwhile physiological disturbances and fasting in migratory phases (smolt and returning adults) could underlie reduced community stability with respect to corresponding non-migratory phases (that is, parr and marine adults, Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although poor in absolute numbers of OTUs (that is, richness), diversity estimates from returning adults were not significantly different from juveniles, suggesting a fairly even frequency distribution of those OTUs present. Dietary complexity in juvenile salmonids could explain rich associated microbial assemblages (Orlov et al, 2006). Meanwhile physiological disturbances and fasting in migratory phases (smolt and returning adults) could underlie reduced community stability with respect to corresponding non-migratory phases (that is, parr and marine adults, Figure 1b).…”
Section: Discussionmentioning
confidence: 99%
“…Growth, development and migration in anadromous S. salar involves a radical shift across an ecological and trophic spectrum (Jacobsen and Hansen, 1999;Orlov et al, 2006). Accompanying the physiological, behavioural and dietary adaptations necessary to cope with transition between freshwater and marine environments (McCormick et al, 2013), significant and potentially adaptive shifts in host-associated microbiota might be expected.…”
Section: Introductionmentioning
confidence: 99%
“…In the wild, domestic salmon exhibit lower fitness than wild salmon and aquaculture escapes can endanger natural populations compromising their viability (Clifford et al 1998;McGinnity et al 1998McGinnity et al , 2003McGinnity et al , 2009. Domestication encompasses genetic changes in life-history traits, which can be subjected to directional selection in farm conditions (Fleming and Einum 1997;Hindar et al 2006) and also in behavioral components such as aggressiveness, mate choice and others (Fleming and Gross 1993;Fleming et al 2000Fleming et al , 2002MignonGrasteau et al 2005;Orlov et al 2006;Castillo et al 2008). As an indicator of such altered behavior, individuals of domestic origin provide most hybrid crosses between Atlantic salmon and brown trout in southern Europe (Castillo et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to hatchery-reared fish from unselected lines, coho salmon (Oncorhynchus kisutch) selected for rapid growth over many generations ingest more food, grow faster and grow more efficiently; fish of the selected line seem to be particularly efficient at using lipids for energy, sparing protein for growth (Figure 7.20;Neely et al 2008). Considering the post-release effects of domestication and captive rearing, wild juvenile Atlantic salmon have fuller stomachs than do hatchery-reared fish soon after release, though this difference is short-lived (Orlov et al 2006) and no differences are reported between domesticated and wild brown trout (Johnsson et al 1996). Finally, captive-bred butterfly splitfins (Ameca splendens) are less likely to feed and more likely to fight than are wild fish (Kelley et al 2006).…”
Section: Domestication and Captive Rearing Effects On Feed Intakementioning
confidence: 99%